2016
DOI: 10.3389/fnhum.2016.00283
|View full text |Cite
|
Sign up to set email alerts
|

Doubt in the Insula: Risk Processing in Obsessive-Compulsive Disorder

Abstract: Extensive cleaning or checking of patients with obsessive-compulsive disorder (OCD) are often interpreted as strategies to avoid harm and as an expression of the widespread belief that OCD patients are more risk-averse. However, despite its clinical significance, the neural basis of risk attitude in OCD is unknown. Here, we investigated neural activity during risk processing using functional magnetic resonance imaging and simultaneously assessed risk attitude using a separate behavioral paradigm in OCD patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 38 publications
(59 reference statements)
1
7
0
Order By: Relevance
“…Additionally, in individuals with SPD, this study found a positive correlation in NE-YBOCS score with increased cortical thickness in the left insula. This finding correlates with previous research that has shown insula activity to correlate directly with risk aversion in individuals with OCD (Luigjes et al, 2016). The finding of this study thus lends partial support for the inclusion of SPD as an ‘obsessive-compulsive related disorder’ in the DSM-5.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, in individuals with SPD, this study found a positive correlation in NE-YBOCS score with increased cortical thickness in the left insula. This finding correlates with previous research that has shown insula activity to correlate directly with risk aversion in individuals with OCD (Luigjes et al, 2016). The finding of this study thus lends partial support for the inclusion of SPD as an ‘obsessive-compulsive related disorder’ in the DSM-5.…”
Section: Discussionsupporting
confidence: 91%
“…In addition to main effects of condition and probability, this analysis also demonstrated a three-way interaction between age group × condition × reward probability for both sides of the VS such that adolescents exhibited the strongest activation for the lowest reward probability (33%) when it was challenging to gain a reward whereas adults demonstrated this for the highest reward probability (88%) when the reward was certain. This points in the direction that adolescents and adults demonstrate a different tolerance toward uncertainty (Luigjes et al, 2016). This could further be linked to regulative aspects of rewardresponses and goal-directed behavior.…”
Section: Discussionmentioning
confidence: 79%
“…Whereas some studies found hyperactivity of the AI/LO hub in OCD 55 , other found hypoactivation. OCD patients displayed reduced serotonin binding in AI/LO 56 and reduced cognitive flexibility correlated with lower activity in the insular region 7 .…”
Section: Clinical Relevancementioning
confidence: 89%